2021
DOI: 10.1108/ijhg-09-2021-0090
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evidence review to understand effective frailty care pathways and their components in primary and community care

Abstract: PurposeDifferent pathways of frailty care to prevent or delay progression of frailty and enable people to live well with frailty are emerging in primary and community care in the UK. The purpose of the study is to understand effective frailty care pathways and their components to inform future service development and pathway evaluation in primary- and community-care services.Design/methodology/approachA rapid evidence review was conducted: 11 research publications met the inclusion criteria and were analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Following full-text screening of 52 records, 39 publications relating to 31 unique reviews were included. (1, 10-39) This included four Cochrane reviews. (1, 10-12) Although most included reviews did not use age or frailty as inclusion criteria, most participants included in the reviews were older and/or had one or more chronic conditions, and the identified Cochrane reviews were included in a rapid review of hospital at home as a component of the frailty pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following full-text screening of 52 records, 39 publications relating to 31 unique reviews were included. (1, 10-39) This included four Cochrane reviews. (1, 10-12) Although most included reviews did not use age or frailty as inclusion criteria, most participants included in the reviews were older and/or had one or more chronic conditions, and the identified Cochrane reviews were included in a rapid review of hospital at home as a component of the frailty pathway.…”
Section: Resultsmentioning
confidence: 99%
“…(1, 10-12) Although most included reviews did not use age or frailty as inclusion criteria, most participants included in the reviews were older and/or had one or more chronic conditions, and the identified Cochrane reviews were included in a rapid review of hospital at home as a component of the frailty pathway. (39) We therefore consider the results of the RES as a whole to be relevant to the use of virtual wards for older people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jagric et al (2022) expand on the issues of hospital finance from a European perspective and examine the effect of healthcare spending on national budgets. Thompson et al (2022) highlight the growing problem of the frail elderly population in the UK and examine evidence for frailty care pathways. They conclude that there is a paucity of current research and make the case for further high quality investigations to create a robust evidence base to use to inform frailty care pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the National institute of Healthcare Excellence (NICE) in the UK recommends systematic assessment of all people over 65, together with early appropriate interventions using specific frailty-care pathways. Thompson et al (2022) report on their scoping exercise to identify the robustness of differing components and outcomes of these pathways in primary and community care services. Findings indicate that many studies are low quality and focus only on single care pathways.…”
Section: Introductionmentioning
confidence: 99%